2017
DOI: 10.1186/s13063-017-1873-z
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of ambulatory red blood cell transfusion on home functional status: study protocol for a pilot randomized controlled trial

Abstract: BackgroundRed blood cell (RBC) transfusion is frequently employed in both ambulatory and hospital environments with the aim of improving patient functional status. In the ambulatory setting, this practice is particularly common in patients with malignancy due to anemia associated with their cancer therapy. Increasingly, the efficacy of this US$10.5 billion per year practice has been called into question. While it is often standard of care for patients with chemotherapy-induced anemia to receive ambulatory RBC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…We showed that transfusion is associated with clinically important improvement in two of these outcomes: walk test distance and fatigue. To define which patients might benefit from transfusion, future studies could include data from wearable monitors to capture effect of RBC on vital signs and physical activity or noninvasive measurement of oxygen saturation to capture tissue response to transfusion . Such data, combined with pretransfusion Hb levels and results of patient‐centered outcome studies like RETRO, will help clinicians personalize the decision to transfuse oncology patients.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that transfusion is associated with clinically important improvement in two of these outcomes: walk test distance and fatigue. To define which patients might benefit from transfusion, future studies could include data from wearable monitors to capture effect of RBC on vital signs and physical activity or noninvasive measurement of oxygen saturation to capture tissue response to transfusion . Such data, combined with pretransfusion Hb levels and results of patient‐centered outcome studies like RETRO, will help clinicians personalize the decision to transfuse oncology patients.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 Sarcopenia, tested via handgrip strength using a hand dynamometer, has been associated with anemia, however, the effect of transfusion is unclear. 56 There is also increasing interest in the use of wearable non-invasive accelerometers 57 to capture the effect of transfusion on daily physical activity.…”
Section: The Need For More Clinical Outcome Measures In Transfusion Trials: Qol Physical Function and Health Economicsmentioning
confidence: 99%
“…Studies on beneficial effects of transfusion in cancer palliative patients are highly inconclusive, and blood transfusion is highly individualized [9]. Rather than being dictated by hemoglobin (Hb) values, transfusion of blood products should be aimed at improving the functional status and QoL [10–13]. Hemoglobin is the most widely accepted standard transfusion trigger in all anemic patients and is usually based on subjective symptoms of easy fatigability, shortness of breath and lethargy [14].…”
Section: Introductionmentioning
confidence: 99%